Plans of Erekle II, King of Kartli-Kakheti as regards the Campaign of Russian Troops in Dagestan in 1775 - Merkviladze, David («Քոփի Փրինթ» տպագրատուն)
In the spring of 1775, in order to punish the Kaitag Utsmi Amir-Hamza, a military expedition of Russian troops under the command of General Medem was sent to Dagestan, after which, at the invitation of Fatali Khan of Derbent, these troops entered the city of Derbent. King Erekle II of Kartli-Kakheti soon responded to this campaign and tried to interest the Russian authorities in a long stay of Russian troops in the city of Derbent, and also suggested that they continue the campaign of troops in the South Caucasus. In a letter to General Medem dated May 6, 1775, Erekle II suggested that he move to the South Caucasus with his army. Promising General Medem all-encompassing support on behalf of all the Christians of Transcaucasia, King Erekle emphasized the ease and further unhindered march of Russian troops. On May 29, King Erekle sent a letter to the head of foreign policy of the Russian Empire, Nikita Panin, in which, reproaching the imperial court for neglecting the interests of the Georgian Kingdom and all Transcaucasian Christians in the last Russian-Turkish war (1768-1774), he asked to order General Medem to continue the campaign in the South Caucasus. According to the King, in this case, given the situation, all the inhabitants of the Transcaucasian khanates, both Christians and Muslims, would declare obedience to Russia. In the words of King Erekle, such an action by the Russian army would be a great consolation for all Christians living between Derbent and his kingdom. 1775 թվականի գարնանը Ղայթաղի ուցմի Ամիր-Համզային պատժելու նպատակով Դաղստան ուղարկվեց ռուսական ռազմական արշավախումբ գեներալ Մեդեմի հրամանատարությամբ, որից հետո Դերբենտի Ֆաթալի խանի հրավերով զորքերը մտան քաղաք Դերբենդ: Այս արշավանքին արձագանքեց Քարթլի-Կախեթի թագավոր Հերակլ II-ը: Վերջինս փորձեց շահագրգռել ռուսական իշխանություններին, որպեսզի Դերբենդում ռուսական զորքերը մնան երկարաժամկետ, ինչպես նաև առաջարկեց նրանց շարունակել զորքերի արշավը դեպի Հարավային Կովկաս:
Keywords: History